2016
DOI: 10.1159/000446952
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Basal Serum Progesterone Prior to Initiate Ovarian Hyper-Stimulation with GnRH Antagonists: A Retrospective Cohort Study

Abstract: Background: The routine assessment of day 3 serum progesterone prior to initiation of ovarian hyper-stimulation with the use of GnRH antagonists is under debate. In this study, we evaluated the clinical utility of this policy. Methods: Retrospective cohort study of women undergoing in vitro fertilization (IVF) with the use of GnRH antagonists aimed at determining the frequency of cases with progesterone levels exceeding the recommended threshold of 1,660 pg/ml and at evaluating whether this assessment may be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…All patients were treated with a GnRH antagonist protocol as previously described [ 21 22 ]. Briefly, both initial dose of FSH and dose adjustments during treatment were chosen on a case-by-case basis according to patients’ characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were treated with a GnRH antagonist protocol as previously described [ 21 22 ]. Briefly, both initial dose of FSH and dose adjustments during treatment were chosen on a case-by-case basis according to patients’ characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Mutlu et al [53] showed an association of basal progesterone above 0.65 ng/ml with preovulatory progesterone rise above 1.5 ng/ml; in this study, cycles with basal progesterone above 1.6 ng/ml were canceled. However, Faulisi et al [158] did not confirm the clinical value of basal progesterone value before the onset of stimulation with GnRH antagonist (day 3).…”
Section: When To Measure It?mentioning
confidence: 95%
“…Patients will be treated according to standard IVF protocols as described elsewhere [12, 13]: since neither the clinicians nor the recruited women will be aware about vitamin D dosage, clinical management of ovarian stimulation will not be conditioned by the study.…”
Section: Methodsmentioning
confidence: 99%